A comparison of the effects of xenobiotics on hepatic haem metabolism - Ziman, Melanie Ruth (Division of Medical Biochemistry and Structural Biology, 2017)
Hepatic microsomal cytochrome P-450 has previously been postulated to be an important factor in determining the rates of hepatic haem biosynthesis and biodegradation. The basis for this proposal is that the haem moiety of cytochrome P-450 appears to be in equilibrium between binding to apocytochrome P-450 and existing in some form in the central hepatic pool of haem concerned with the regulation of the haem metabolic pathways. Consequently, any change in the levels of hepatic cytochrome P-450 would be anticipated to affect the pathways of hepatic haem biosynthesis and biodegradation. At the onset of this project, relatively few chemical agents were known to destroy cytochrome P-450 (either by degradation of the haem moiety of, or dissociation of the haem moiety from hepatic microsomal cytochrome P-450) and to affect hepatic haem biosynthesis and/or haem biodegradation (e.g. AIA, Cs₂ and various metals). We thus attempted to further establish the relationship between the ability of compounds to affect hepatic cytochrome P-450 and to affect hepatic haem metabolism in vivo, using the three anaesthetic agents, fluroxene, halothane and trichloroethylene. During the preparation of this thesis, several other chemicals have been found which destroy cytochrome P-450 and affect hepatic haem metabolism (e.g. norethisterone, morphine). In addition to the above, it has been attempted to clarify the roles of the degradation of different forms of cytochrome P-450 and of the different mechanisms of destruction of cytochrome P-450 in the control of hepatic haem metabolism. The three anaesthetic agents, fluroxene, halothane and trichloroethylene were chosen for study since they destroy cytochrome P-450 by apparently different mechanisms. Both fluroxene and trichloroethylene specifically degrade the haem moiety of different forms of cytochrome P-450, but fluroxene converts the haem moiety of cytochrome P-450 to an N-substituted porphyrin, while TCE apparently degrades the haem into uncoloured products. In contrast, halothane appears to degrade the haem of cytochrome P-450 to uncoloured products as well as to facilitate the dissociation of haem from intact cytochrome P-450.